Cabeça Dinossauro e Nheengatu: uma leitura bakhtiniana das letras de música dos Titãs - Oliveira, Cláudia de Fátima (2019)
In the 1980s, Brazil went through the post-dictatorial period and in 1985, through democratic openness. In this scenario, the São Paulo band Titãs released the LP Cabeça Dinossauro, with lyrics of a critical, ideological and ironic nature, before the Church, State and Family institutions. In 2015, the band released the CD Nheengatu, with criticisms to the same institutions. The aim of this study is to investigate how the letters maintain dialogical relations between themselves and the social body at different times and places, from the reflections of the Russian philosopher Mikhail Bakhtin. The statements mark the historical, political and social context at different times. The compositions deal with social issues through the letters of “Polícia”, “Família”, “Igreja”, “Flores pra Ela”, “Fardado” and “Senhor”. Therefore, the letters will be analyzed from a qualitative analysis, amid the dialogical questions. For theoretical support, Bakhtin's (2006) considerations bring the idea that discourses represent a constitutive otherness, understanding that the value judgments expressed by a speaker embody the discourses of others. Thus, the dialogue between the letters occurs from the ideological insertions in relation to the historical and social context lived by the authors and transmitted to the contemplators for an interpretative assimilation. It is therefore concluded that in different times and spaces, although there were differences between the situations that govern relations in the analyzed institutions, there are many similarities between them and that the places of power practically remain the same, although chronotopes different.